HYDROMORPHOLOGICAL ASSESSMENT OF THE LOWER HUNGARIAN DRAVA SECTION AND ITS FLOODPLAIN - DÉNES LÓCZY; JÓZSEF DEZSŐ; SZABOLCS CZIGÁNY; ERVIN PIRKHOFFER (Acta Geographica Debrecina. Landscape & Environment Series)
The hydromorphological properties of rivers and their floodplains receive increased attention both in basic research and water management. A comparison of hydromorphological parameters before and after river regulation (involving floodplain drainage) provides important information for river management, particularly floodplain rehabilitation. The paper assesses a selected reach of the Drava River and the corresponding floodplain utilising two international approaches, the REFORM framework and the Italian Morphological Quality Index.